The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1111/asj.12063
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study for fatty acid composition in Japanese Black cattle

Abstract: Fatty acid composition is one of the important traits in beef. The aim of this study was to identify candidate genomic regions for fatty acid composition by genome-wide association study with 50 K single nucleotide polymorphism (SNP) array in Japanese Black cattle. A total of 461 individuals and 40 657 SNPs were used in this study. We applied genome-wide rapid association using mixed model and regression (GRAMMAR) and genomic control approaches to estimate the associations between genotypes and fatty acid comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
52
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 39 publications
(35 reference statements)
3
52
3
1
Order By: Relevance
“…Previous studies suggested that polymorphism of the SCD gene should affect the FA composition of fatty acids in beef (Matsuhashi et al 2011;Li et al 2012; M a n n e n et al 2012; Ishii et al 2013). Our results, however, did not confirm this claim.…”
Section: Discussioncontrasting
confidence: 90%
“…Previous studies suggested that polymorphism of the SCD gene should affect the FA composition of fatty acids in beef (Matsuhashi et al 2011;Li et al 2012; M a n n e n et al 2012; Ishii et al 2013). Our results, however, did not confirm this claim.…”
Section: Discussioncontrasting
confidence: 90%
“…The fatty acid synthase (FASN) locus, contained in this region, was proposed as putative candidate gene affecting milk fatty acid composition. In the present research, the marker ARS-BFGL-NGS-39328 was found associated to FP, thus confirming the presence of a QTL for fat traits on BTA19 as suggest by Ishii et al (2013) (Supplementary Material S1).…”
Section: Discussionsupporting
confidence: 84%
“…Recently, in a GWAS on the Japanese Black cattle breed, Ishii et al (2013) identified a significant number of SNPs affecting milk fatty acid composition in a region between 49 and 52 Mb of the BTA19. The fatty acid synthase (FASN) locus, contained in this region, was proposed as putative candidate gene affecting milk fatty acid composition.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms in chka have been identified to be associated with human diabetes [41]. The tanc2 gene has been investigated as a candidate gene for the locus on BAT19 where BTB-00755526 at 48.24 Mb was associated with mirystic acid (C14:0) of intramuscular adipose tissue in Japanese Black cattle [42]. Interestingly, this gene was up-regulated in the high-fat groups compared to the low-fat groups in pig longissimus muscle at 110 kg Body Weight [43].…”
Section: Discussionmentioning
confidence: 99%